MAX BLECHER’S CENTRAL EUROPEAN AFFINITIES - GLĂVAN, Gabriela (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Max Blecher’s Central European Affinities. Max Blecher’s connections with the Central European literary imaginary, which scholars have established through readings that place Blecher in the proximity of authors such as Bruno Schulz or Franz Kafka, could be revisited not only comparatively, but also by tackling some key issues in his work and biography that may confirm the writer’s belonging to this vast intellectual territory. Provincial spaces, marginality, uncertainties regarding identity, existential confusion, immaturity, the pervasiveness of objects and of the artificial, they all reveal a perspective upon literature that may function, in the absence of a geographical belonging, as a bridge and connection between worlds that mirror each other’s essence and difference. REZUMAT. Max Blecher – afinități central-europene. Conectarea lui Max Blecher la imaginarul central-european, consolidată critic prin asocieri cu Franz Kafka sau Bruno Schulz, poate fi rediscutată nu doar din perspectivă comparativă, ci și prin explorarea unor aspecte ce-i pot justifica direct apartenența la acest vast teritoriu intelectual. Provincia, marginalitatea, incertitudinea identității, confuzia, imaturitatea, invazia obiectelor și a artificialului revelează o viziune literară ce poate funcționa, în absența unei apartenențe geografice, ca punte și conector între lumi ce-și expun în oglindă specificul și diferența. Cuvinte-cheie: literatura central-europeană, identitatea, provincia, perifericul, evreitatea